The effectiveness of albendazole against hookworm infections and the impact of bi-annual treatment on anaemia and body mass index of school children in the Kpandai district of northern Ghana. - Buhari A Hamidu; Edward J Tettevi; John A Larbi; Bright K Idun; Elias K Asuming-Brempong; Mike Y Osei-Atweneboana (PLoS ONE, 2024)
The impact of the Global Programme to Eliminate Lymphatic Filariasis (GPELF) (initiated in 2000 in Ghana and ran for 12 years) in mitigating soil-transmitted helminth (STH) infections in LF-endemic areas is unknown. During a 1-year hiatus which ensued between 2011 and 2012, a longitudinal study was conducted to determine GPELF effect on hookworm infections in selected communities involved in the programme since its inception, while measuring the effectiveness of biannual ALB treatments on schoolchildren living in such communities. A total of 399 school children aged 3 to 18 years were randomly selected from four communities in the Kpandai district of northern Ghana. Each presented a single stool sample at baseline, 21 days post-treatment, at the 3rd and 6th months, 21 days post-second intervention (i.e. following sample collection and treatment with ALB in the 6th month), and in the ninth month of the study period. Haemoglobin (hb) levels were also measured at all time points using finger prick blood samples and a URIT digital test kit. Each participant submitting a sample, was treated with a single-dose ALB (400mg) at baseline and in the sixth month. Stool samples were processed by preparing duplicate Kato-Katz slides per sample, and examined by microscopy. The Body Mass Index-for-age z-scores (BAZ) of participants were assessed following the determination of BMIs at each time point by measuring their height and weight with a stadiometer and weighing scale. Overall hookworm prevalences were 25.68% (95% CI = 20.51-31.75) at baseline, 11.18% (95% CI = 7.87-15.41) 21 days post-treatment, 11.78% (95% CI = 8.38-16.11) and 6.95% (95% CI = 4.41-10.43) in the 3rd and 6th months, 0.91% (95% CI = 0.19-2.65) 21 days post-second intervention, and 8.46% (95% CI = 5.62-12.23) in the ninth month. Observed overall faecal egg count reduction rates (ERRs) were 94.21% (95% CI = 81.50%- 100.00%) 21 days after baseline treatment, 97.70% (95% CI = 85.08-100.00) and 96.95% (95% CI = 84.18%- 100.00%) in the 3rd and 6th months, 99.98% (95% CI = 86.42%- 100.00%) 21 days post-second intervention, and 17.18% (95% CI = 14.07%- 20.67%) in the 9th month. Respective cure rates (CRs) were 62.35% (95% CI = 46.71-81.56%), 85.88% (95% CI = 67.32-100.00%), 87.06% (95% CI = 68.36%- 100.00%), 98.82% (95% CI = 78.83%- 100.00%), and 36.36% (95% CI = 9.91%- 93.11%). Additionally, increases in the percent frequency of 'normal hb' (p < 0.01) were observed across the study time points, whilst 'normal BAZ' cases remained high (from 94.87% to 98.87%) throughout the study period. These findings primarily indicate satisfactory effectiveness of ALB which may be maintainable in mass drug administration programmes by the modification of treatment strategies from annual to bi-annual regimes. This could minimize the likelihood of emerging poorly-responding hookworm phenotypes in Ghana. Additionally, a positive impact of bi-annual treatment on participant anaemia status is herein indicated with particular regard to the school children in our cohort.